2017
DOI: 10.1589/jpts.29.1276
|View full text |Cite
|
Sign up to set email alerts
|

Effects of central and unilateral posteroanterior mobilization on cervical lordosis, muscle stiffness and ROM in patient with ankylosing spondylitis: case study

Abstract: [Purpose] The aim of this study was to determine the effects of central and unilateral posteroanterior (PA) mobilization on cervical lordosis, muscle stiffness and range of motion in a patient with ankylosing spondylitis (AS). [Subject and Methods] The subject of this case study was diagnosed with AS in 1997. At baseline, variance was measured without any intervention during the first 3 days (2016.6.13–2016.6.15). Cervical PA mobilization was applied to each segment from C2–C7 from the 4th to the 11th day for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…Furthermore, Park et al [ 35 ] found differences in cervical muscle frequency and stiffness between patients with cervicogenic headache and healthy individuals, but not in decrement as observed in our patients, which could mean that elasticity does fit the same behavior pattern as other mechanical properties when spinal muscles are assessed. This author also reported a case study [ 36 ] of an axSpA patient, analyzing cervical muscles pre- and post-treatment for central and unilateral posteroanterior mobilization. In this study, the treatment was effective in decreasing muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Park et al [ 35 ] found differences in cervical muscle frequency and stiffness between patients with cervicogenic headache and healthy individuals, but not in decrement as observed in our patients, which could mean that elasticity does fit the same behavior pattern as other mechanical properties when spinal muscles are assessed. This author also reported a case study [ 36 ] of an axSpA patient, analyzing cervical muscles pre- and post-treatment for central and unilateral posteroanterior mobilization. In this study, the treatment was effective in decreasing muscle stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar measurements were carried out by placing the probe of the device perpendicular to the muscular belly of the erector spinal column, 2.5 cm from the midline of the spinous process of L5 [ 46 ] ( Figure 1 a). For the cervical measurements, the semispinalis capitis muscles at C4 level were assessed [ 31 , 47 ] ( Figure 1 b). The order of assessments (right/left) was randomized by a randomization plan generator ( , accessed on 10 October 2018).…”
Section: Methodsmentioning
confidence: 99%
“…MT'nin kas sertliği üzerine etkileri, farklı popülasyonlarda ve farklı değerlendirme yöntemleri ile incelenmiştir. [26][27][28][29] Servikojenik baş ağrısında, servikal mobilizasyonunun servikal kas sertliği üzerine etkisinin "shear-wave elastografi (SWE)" ile incelendiği bir olgu çalışmasında, tek seans servikal mobilizasyondan sonra TRP kas sertliğinin azaldığı bildiril- miştir. 26 Park ve ark.…”
Section: Discussionunclassified
“…yaptığı olgu çalışmasında, her gün yapılan 8 seans servikal mobilizasyonun ankilozan spondilitli bir hastada kas sertliğini azalttığı bildirilmiştir. 27 Kim ve ark. TRP kasında tetik noktaları bulunan akıllı telefon kullanıcılarında SKM ve suboksipital kaslara uygulanan yumuşak doku tekniklerinin kas sertliğine etkisini miyotonometrik bir cihaz ile incelemiş ve yumuşak doku tekniklerinin SKM ve TRP kas sertliğini azalttığını bulmuşlardır.…”
Section: Discussionunclassified